STUDY OF WAYS TO REDUCE THE VISCOSITY OF SUNFLOWER LECITHIN - A. Demydova; V. Yevlash; O. Аksonova; O. Priss (Harčova Nauka ì Tehnologìâ, 2023)
Today, lecithin is the most important by-product of oilseed processing due to its numerous technological properties.  Food industry technologists use lecithin as an emulsifier, wetting agent, stabilizer, viscosity regulator, crystal formation, etc. One of the main disadvantages of sunflower lecithin is the tendency to increase viscosity (plasticization) during storage. Such lecithin is difficult to use. Therefore, obtaining liquid lecithin with a viscosity of less than 12 Pa s (at 25 °C), which does not increase during its storage, is one of the urgent tasks of enterprises for the extraction and processing of vegetable fats. The article compares diluents of different types. Diluents of fatty nature - sunflower oil, oleic acid and its ethyl ester are characterized by a significantly lower viscosity compared to lecithin, therefore they can act as diluents that do not affect the quality of lecithin. However, their amounts are too large to achieve the goal of obtaining liquid lecithin. These amounts significantly reduce the "acetone insoluble" lecithin index. That is, oils, their acids and esters cannot be recommended for reducing the viscosity of lecithins in industry. It has been shown that the efficiency of divalent calcium salts as diluents is much greater, even at low concentrations of these substances. It has also been proven that the introduction of diluents must be carried out before the stage of drying the wet gum. To obtain liquid lecithin from plasticized lecithin, approximately twice as high concentrations of diluents are required compared to the preventive approach - the introduction of diluents into a wet gum. To obtain liquid sunflower lecithin from a wert gum to which diluents were added, the effective concentrations of diluents are as follows,%: sunflower oil - 13, oleic acid - 5, ethyl ester of oleic acid - 4, calcium chloride - 0.35, calcium acetate - 0.4, calcium orthophosphate - 0.4, concentrated phosphoric acid - 2. It is most expedient to use calcium salts in order to obtain high quality liquid lecithin.